LOW-TEMPERATURE HEAT CAPACITY OF STRONTIANITE SRCO3(C) - Gurevich V.M. (My University, 2001)
The temperature dependence of strontianite SrCO3(c) heat capacity was determined within the range 0-336 K. It was measured within 22.13-336.94 K and calculated below 22.13 K. The experimental data were approximated with an equation expressing C-p(0)(T) of strontianite through the sum of Debye's, Kieffer's, and Einstein's functions. This dependence allowed the extrapolation of C-p(0)(T) to 0 K at temperatures below 22.13 K, which were not experimentally studied. The following values were obtained for the standard heat capacity, entropy, and enthalpy change of strontianite SrCO3(c) at 298.15 K: C-p(0)(298.15 K) = 86.52 +/-0.15 J mol(-1) K-1, S-0(298.15 K) = 100.01 +/-0.24 J mol(-1) K-1, H-0(298.15 K) - H-0(0) = 15.686 +/-0.022 kJ mol(-1).